Empowerment Leadership: Cultivating Cultural Intelligence and Its Effects on Job Flourishing - Fikri, Khusnul; Astarina, Ivalaina; Rifa’i, Ahmad; Setianingsih, Rahayu; Abunawas, Abunawas; Alviani, Devi (Jurnal Aplikasi Manajemen, 2024)
Understanding human behavior and cultural dynamics within a company becomes crucial in the competitive business era, where job flourishing, involving satisfaction, motivation, and professional development of employees, plays a key role in ensuring optimal performance and sustainability of the organization. This study aims to fill the gap by exploring the relationship between empowering leadership and job flourishing in the context of organizations in Indonesia, using a quantitative method with a cross-sectional design and focusing on a micro-level analysis. The population of this study was 250 employees, using Krejcie and Morgan's (1970) formula and simple random sampling technique, 154 respondents were obtained. We distributed closed questionnaires with a 7-point Likert scale, and data were processed using SEM PLS. The study shows that although empowerment leadership does not directly affect employees' job flourishing significantly, its effectiveness depends on cultural intelligence. This confirms that successful leadership approaches in the workplace not only pay attention to empowerment but also the leader's ability to understand and adapt to cultural diversity in the work environment. Leaders with cultural intelligence need to nurture and develop employees' cultural intelligence levels to interact better amidst cultural differences. Thus, the integration between empowerment leadership and cultural intelligence becomes key to creating a work environment that supports job flourishing.